Current Opinion in Plant Biology - Current Opinion in Plant Biology (Elsevier, 2026)
Current Opinion in Plant Biology builds on Elsevier's reputation for excellence in scientific publishing and long-standing commitment to communicating high quality reproducible research. It is part of the Current Opinion and Research (CO+RE) suite of journals. All CO+RE journals leverage the Current Opinion legacy - of editorial excellence, high-impact, and global reach - to ensure they are a widely read resource that is integral to scientists' workflow.
FI 1
Q1
Keywords: Life Sciences; Plant Science; Ciencia de las plantas; Acuerdos transformativos; Transformative agreements; Biología vegetal; Biología celular; Fisiología